The Impact of Ethinyl Estradiol on Metformin Action on Prolactin Levels in Women with Hyperprolactinemia - Krysiak, Robert; Szkróbka, Witold; Okopień, Bogusław (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Metformin reduced prolactin levels only in women with hyperprolactinemia.Objective The purpose of this case-control study was to compare metformin action on lactoctrope function between women receiving oral contraceptive pills and women not using hormonal contraception.Methods The study included two groups of matched women with elevated prolactin levels and new-onset prediabetes or diabetes. The first group consisted of 20 women using oral contraceptive pills for at least 12 months before entering the study, while the second group included 20 patients not using any hormonal contraception. Over the whole study period, all women were treated with metformin (1.7–3 g daily). Circulating levels of glucose, insulin, prolactin, thyrotropin, free thyroid hormones, adrenocorticotropic hormone, gonadotropins and insulin-like growth factor-1 were measured at the beginning and at the end of the study (16 weeks later).Results Thirty-eight patients completed the study. Metformin reduced plasma glucose levels and improved insulin sensitivity but the latter effect was stronger in women receiving oral contraceptive pills than in women not using any contraception. Although metformin treatment decreased plasma prolactin levels in both study groups, this effect was stronger in women taking oral contraceptive pills. Only in this group of women, metformin increased plasma luteinizing hormone levels. The changes in plasma prolactin correlated with their baseline insulin sensitivity and the effect of metformin on insulin sensitivity. Metformin did not affect plasma levels of thyrotropin, free thyroxine, free triiodothyronine, follicle-stimulating hormone, adrenocorticotropic hormone and insulin-like growth factor-1.Conclusions The obtained results suggest that the effect of metformin on overactive lactotropes depends on estrogen levels.
Keywords: insulin sensitivity; lactotropic cells; metformin; pituitary